Socio-economic analysis on the role of local government in developing the abalone industry in Korea (Research in Agriculture Livestock and Fisheries, 2016)
Many Koreans regard abalone (Haliotus discus hannai) as a desirable luxury food because of its limited availability and high price. Abalone aquaculture was developed during the late 2000s, and production has greatly increased in Korea, reaching 9,147 tons in 2014. Policy experts said this trend means many fishers who cultivate abalone could increase their income. However, their incomes had not increased since fishers started cultivating abalone, because a conventional addition was applied to abalone transactions. The distribution structure for abalone products relies almost entirely on wholesalers instead of fisheries cooperatives, which are commonly used for other types of seafood products. Therefore, a new distribution structure was required in the Korean abalone industry. The objective of this study was to document how the establishment of an abalone cooperative by the local government has affected fishers income and production since 2009. This research was conducted in Wando District in South Jeolla Province, which accounts for over 90% of the domestic abalone production. Wholesalers, fishers, and a public officer were interviewed. A shift from a wholesalercontrolled distribution structure to a cooperative run by the local government helped to reduce the addition and increase fishers incomes overall.Res. Agric., Livest. Fish.3(2): 345-353, August 2016